PENDIDIKAN ANAK DALAM AL-QUR’AN - Sulaiman Saat (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2010)
Education in the context of taking care of, growing and leading children is derived from the meaning of ‘rab’ (in Arabic). It is mentioned many times in the Qur’an and reflects the nature of the Almighty. The Almighty God is Lord of the world and protects it. The word ‘tarbiyah’ which means ‘education’ is derived from this context. According to the Qur’an, there are different methods can be applied in teaching, such as: being example, building habit action, giving advice and controlling. The content of education, according to the Qur’an, includes Theology, Ethics, the study of religious practices, Physics, Logics, and Sociology.